Beach Monitoring and Morphological Response in the Presence of Coastal Defense Strategies at Riccione (Italy) - Claudia Romagnoli; Flavia Sistilli; Luigi Cantelli; Margherita Aguzzi; Nunzio De Nigris; Maurizio Morelli; Maria Gabriella Gaeta; Renata Archetti (Journal of Marine Science and Engineering, 2021)
The coastal area at Riccione, in the southern Emilia-Romagna littoral region, is exposed to erosive processes, which are expected to be enhanced by climate change. The beach, mostly composed of fine sand, is maintained through various defense strategies, including frequent nourishment interventions for balancing the sediment deficit and other experimental solutions for reducing coastal erosion. Artificial reshaping of the beach and “common practices” in the sediment management redefine the beach morphology and the sediment redistribution almost continuously. These activities overlap each other and with the coastal dynamics, and this makes it very difficult to evaluate their effectiveness, as well as the role of natural processes on the beach morphological evolution. Topo-bathymetric and sedimentological monitoring of the beach has been carried out on a regular basis since 2000 by the Regional Agency for Prevention, Environment and Energy of Emilia-Romagna (Arpae). Further monitoring of the emerged and submerged beach has been carried out in 2019–2021 in the framework of the research project STIMARE, focusing on innovative strategies for coastal monitoring in relation with erosion risk. The aim of this study is to assess the coastal behavior at the interannual/seasonal scale in the southern coastal stretch of Riccione, where the adopted coastal defense strategies and management actions mostly control the morphological variations in the emerged and submerged beach besides the wave and current regime. The topo-bathymetric variations and erosion/accretion patterns provided by multitemporal monitoring have been related to natural processes and to anthropogenic activities. The morphological variations have been also assessed in volumetric terms in the different subzones of the beach, with the aim of better understanding the onshore/offshore sediment exchange in relation with nourishments and in the presence of protection structures. The effectiveness of the adopted interventions to combat erosion, and to cope with future climate change-related impacts, appears not fully successful in the presence of an overall sediment deficit at the coast. This demonstrates the need for repeated monitoring of the emerged and submerged beach in such a critical setting.